2019
DOI: 10.3390/rs11151766
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sentinel-1 Synthetic Aperture Radar (SAR) Images and Open-Source Software for Cultural Heritage: An Example from Paphos Area in Cyprus for Mapping Landscape Changes after a 5.6 Magnitude Earthquake

Abstract: Active satellite remote sensors have emerged in the last years in the field of archaeology, providing new tools for monitoring extensive cultural heritage landscapes and areas. These active sensors, namely synthetic aperture radar (SAR) satellites, provide systematic datasets for mapping land movements triggered from earthquakes, landslides, and so on. Copernicus, the European program for monitoring the environment, provides continuous radar datasets through the Sentinel-1 mission with an almost worldwide cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…In the light of the above, it becomes evident that relative displacements have occurred in the areas of the UNESCO Heritage sites. The displacements retrieved from the current interferometric analysis are also supported by the findings of a similar study, emanated from the same seismic event [16]. Table IV below reproduces the quantification of the displacements detected.…”
Section: Archaeological Sitessupporting
confidence: 85%
See 2 more Smart Citations
“…In the light of the above, it becomes evident that relative displacements have occurred in the areas of the UNESCO Heritage sites. The displacements retrieved from the current interferometric analysis are also supported by the findings of a similar study, emanated from the same seismic event [16]. Table IV below reproduces the quantification of the displacements detected.…”
Section: Archaeological Sitessupporting
confidence: 85%
“…As it is evident, the coherence map is different for both orbits. A threshold of around the 0.60 coherence value is usually used to exclude areas with noise [16].…”
Section: Coherence and Cross-comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…All the Sentinel missions were released under an open data policy to foster knowledge, innovative applications, and advanced developments. In particular, S-1 data were used for the monitoring of cultural heritage (CH) [12], and recent pioneering studies have highlighted that S-1 can be useful to extract information regarding the contemporary and past…”
Section: Introductionmentioning
confidence: 99%
“…Increased interest from the scientific community for monitoring archaeological areas through satellite imagery has been reported in the recent past (Luo et al 2019 Agapiou & Lysandrou 2015). These studies have shown the benefits of using Earth Observation as a systematic tool for monitoring natural and man-made hazards (Tzouvaras et al 2019), including also looted areas (Cigna et al 2014;Tapete et al 2013).…”
Section: Introductionmentioning
confidence: 99%